Wpływ wprowadzenia maksymalnych limitów odsetek od kredytów na warunki działalności banków w Polsce i na ich klientów na tle doświadczeń europejskich - Zaleska, Małgorzata (Impact of the introduction of maximum limits for interest on credit on the conditions of operations of co-operative banks in Poland and on their customers as compared with the european experience, 2006)
Considering the possibilities and the need for the introduction of the legal rules in Poland regarding the maximum limits for the interest on credits, the following has been analyzed: the extent to which Polish population is familiar with banking products with the particular interest on the indebtedness level and the factors influencing it; experience gained by other countries as a result of the implementation of maximum limits for the interest on credits; the effects of the implementation of maximum limits for the interest on credits in a particular country. The analysis which have been carried out allowed to conclude that: the experience gained by other countries indicates the negative impact of the implementation of the maximum limits for the interest on credits on the economic growth and the operational conditions of the players on the financial market (it mainly refers to the consumer credit market and credit card market); the legal regulations in the field of maximum limits for the interest on credits in Poland may be easily evaded.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1128, s. 109-117